Preferred practice patterns of endophthalmitis management and prevention: A survey among the members of Vitreoretinal Society of India – Study by the VRSI study group - Deepanshu Agrawal; Anil B Gangwe; Koushik Tripathy; Pradeep Sagar; P Mahesh Shanmugam; Manisha Agrawal; Deepshikha Agrawal; Raj Vardhan Azad (Indian Journal of Ophthalmology)
Purpose: To assess the preferred practice patterns of endophthalmitis management and prophylaxis among the members of Vitreo Retina Society of India (VRSI). Methods: An online questionnaire was circulated among the VRSI members, enquiring details on clinical presentation of endophthalmitis, initial management protocols of acute and chronic endophthalmitis, usage of antibiotics, steroids, and silicone oil (SO) in endophthalmitis, and prophylaxis followed for prevention of endophthalmitis. Results: A total of 313 (20.2%) responses were obtained. The mean age of the respondents was 43.2 ± 0.5 years, and there was a male predominance (n = 231, 73.8%). Post-cataract surgery endophthalmitis (PCSE) was the most common (n = 273, 87.2%) reported variant, followed by post-traumatic endophthalmitis (PTE) (n=37,11.8%). Over 50% (n = 181, 57.8%) of respondents followed Endophthalmitis Vitrectomy Study (EVS) guidelines for acute PCSE and about 60% (n = 194, 61.9%) would not extrapolate EVS guidelines to other forms of endophthalmitis. A total of 159 (50.8%) respondents preferred using a vitreous/anterior chamber tap with needle, and vitreous biopsy with vitrector was preferred by 117 (37.3%) respondents. Vancomycin–ceftazidime remains the preferred combination of empirical intravitreal antibiotics (IVAs), and 169 (54%) preferred injecting intravitreal steroids along with IVA. About one-fourth (n = 90, 28.8%) of the respondents preferred pars plana vitrectomy as the initial management for PCSE. SO was used mostly in cases with PTE (n = 176, 56.2%). Prophylactic measures to prevent endophthalmitis varied among the respondents. Conclusion: Majority of the Indian vitreoretinal surgeons felt the need for amendment in the EVS guidelines, but would prefer to follow the EVS guidelines for managing endophthalmitis at present.